The Role of Audio-Visual Media to Overcome Problems Learning English Language - Panduwinata, Tiara (Yayasan Nurma Gemilang, 2024)
This journal discusses the role of audio-visual media in overcoming problems that occur in English learning at STAI Sultan Syarif Hasyim Siak. This research aims to explore the effectiveness of using audio-visual technology, such as digital learning videos, in English language learning. The research method uses qualitative methods through classroom observations, interviews, and documentation. The results of the research show that the problems in English language learning that can be overcome by using audio-visual technology are: 1) By using audio-visual media, it becomes easier for lecturers to demonstrate teaching materials or learning materials to students so that they can improve the understanding of students who find it difficult to understand the material; 2) lecturers can attract the interest and attention of students who lack motivation to learn English; 3) improve the language skills of students who have difficulty pronouncing English; and 4) prepare students to face educational challenges in the digital era. The practical implication of this research is that the role of audio-visual media can support learning strategies that are more adaptive and responsive to the demands of technological developments and overcome problems that occur in the English learning process